Parent Perspectives on Adolescent Gender-Based Violence as a Public Health Issue in Medellín, Colombia: A Qualitative Study - David Sanchez Villa; Mariangela Castro-Arteaga; Luis Fernando Alonso Mendoza; Claudia Patricia Pérez; Amaya Perez-Brumer; Julien Brisson (Hispanic Health Care International, 2026)
Introduction Gender-based violence (GBV) is a major public health concern affecting adolescents across Latin America. Yet, little is known about how parents, as key figures in adolescents’ social environments, understand these risks. This study explored parental perspectives on adolescent GBV in Colombia. Methods Between February to April 2024, we conducted 28 semi-structured interviews with parents of adolescents aged 10–19 in the metropolitan area of Medellín, Colombia. Interviews were transcribed verbatim and analyzed using reflexive thematic analysis. Results Twenty-eight parents participated; most were women (79%), and collectively they were caregivers to 35 adolescents with a median age of 14. Parents consistently described GBV as an urgent and pervasive threat to adolescent well-being, particularly in relation to sexual abuse, dating violence, and the normalization of harm. Machismo emerged as a central cultural and structural determinant shaping gender norms and adolescents’ vulnerability. Family-level dynamics – including silence, fear, and modeled behaviors – were perceived as contributing to cycles of violence. Parents also emphasized prevention through early child education on abuse, active communication with adolescents, and clear guidance on boundaries and respectful relationship practices. Conclusion Parents’ perspectives highlight the need for culturally grounded, caregiver-centered public health interventions to address GBV among adolescents in Colombia.